Study on the non-motorized transport in Shanghai, China - Ying, Guan; Yordphol Tanaboriboon; Mori, Hiroshi; Shimazaki, Toshikazu; Canadian International Development Agency (Bangkok : Asian Institute of Technology, 1992)
In Sha ng hai , non - motorized tran s port plays a most important rol e in the urba n transportat i on system . This study foc uses on the non- mo torized transport c haracteristics in particular t he bicycles and pedestrians in Shanghai . For bicycle transport mode , t his study concentrates on the u sers c haracteristics and speed c haracteri st i cs . For pedestrian , walking speeds of Shanghai pe destrians ar e the main aim of this research . The bicycle users c haracteristics data were col l ected through quest i onnaire s urveys while b icycle and pedestrian speed data were obtained by modified moving bicycle test and photographi c technique, respectively. The results revealed t hat household bicycle ownersh ips were very high , a lmost 67 percent of household h ad at l east two bicycles . More than 75 percent of bicycl e users were government off i cers and workers and their main trip purpose of using b i cycles was work trips. The average riding time was found to be 25.3 minutes and males were able to ride longer t h an females . Meanwhile, results indicated that bicycle users in this city can bear l onger riding time of maximum 41 minutes . The result s of riding speeds indicated that bicycle facilities affect t h e riding speeds . The highest riding speed was obtained o n a bike path, whic h r epr esented by 15 .26 kph . It is also found that ages and sexes i nfl uenced their riding speeds, young males s howed the hig hest riding speeds (16.17 kph} among all groups. Pedestrian walking speed studies s howed that mean walking speeds at walkways were faster than a t crossway, which were 69.57 m/min and 62 . 14 m/min, respectively. The Chinese pedestrians walking speed were found to be slower compared with other countries.
Thesis (M.Eng.) - Asian Institute of Technology
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Keywords: Cycling paths -- China -- Shanghai; Bicycles -- China -- Shanghai